Effects of a Visual Representation of Search Engine Results on Performance, User Experience and Effort - Gonzalez-Ibanez, R; Fuenzalida-Navarrete, G; Proaño-Rios, V; Martinez-Ramirez, G (John Wiley and Sons Inc, 2017)
Search engine results have been predominantly displayed as a vertical list of textual items. While this presentation approach has proven effective in well-known search engines, there are search tasks where users could benefit from other presentation styles. In this study, we compare two approaches to displaying search engine results. The first corresponds to a traditional one (vertical list) with 10 results per page, whereas the second one consists of a visual representation of 400 results displayed at once. We perform this comparison in the context of a recall-oriented search task where multiple relevance criteria must be satisfied. Our study focuses on the effects of the two representation approaches on performance, user experience and effort. Results from this study suggest that exposing participants to a large number of search results using adequate visual cues helps to reduce visual and physical effort without compromising to a great extent performance and user experience. More importantly, the exposure to a large volume of results does not increase cognitive load, nor worsen affective experience. Copyright © 2017 by Association for Information Science and Technology